Discipline, Devotion, and Dissent: Jewish, Catholic, and Islamic Schooling in Canada By Graham P. McDonough, Nadeem A. Memon, and Avi I. Mintz, eds. (Waterloo, Canada: Wilfrid Laurier University Press, 2013. 272 pages.) (American Journal of Islam and Society, 2014)
During the 2007 provincial election campaign, Conservative party candidateJohn Tory proposed extending government funding to all faith-based schoolsin Ontario. This was met with strong public and media opposition due to fearsof radicalization and indoctrinating students in religious beliefs considered outdatedand a threat to Canadian norms (particularly with Islamic schools). It iswith this anecdote that editors Graham P. McDonough, Nadeem Memon, andAvi L. Mintz introduce Discipline, Devotion, and Dissent: Jewish, Catholic,and Islamic Schooling in Canada. As they note, the impassioned debate surroundingTory’s election promise, as well as his ensuing loss, indicate that religiouseducation is a particularly contentious topic in an increasingly secularsociety. And yet there is surprisingly little scholarly literature on this topic.The editors seek to address this gap through this excellent and muchneeded contribution to the field. Focusing solely on Catholic, Islamic, and Jewishschools, which make up the vast majority of Canada’s full-time religiousschools, the editors seek not to provide an overview of religious education, butto address three issues: The schools’ aims and practices, how they “negotiatethe tension between the demands of the faith and the expectation that they educateCanadian citizens,” and how they “respond to internal dissent.” ...